Manajemen Mutu Pendidikan Islam - Alfian Tri Kuntoro (Jurnal Kependidikan, 2019)
Abstact This study aims at offered to improve quality of Islamic education that is able to develop abilities optimally, and is able to establish the character and civilization of the school. Efforts to improve the quality of Islamic education are not at once, but also based on improving the quality of each component of education. The focus of management for improving the quality of education lies in the process or system of achieving the goals of the school organization itself. Management of improving the Islamic education quality in schools is an effort to improve the quality of Islamic education centered on school education itself, apply a set of techniques based on the availability of quantitative and qualitative data, and empower all elements of the school to sustainably increase capacity and the ability of school organizations to meet the needs of students and the community.Keywords: Education Management, Quality, and Islamic Education Abstrak Penelitian ini bertujuan untuk memberikan tawaran bagi peningkatan mutu pendidikan Islam yang mampu mengembangkan kemampuan secara maksimal, dan mampu membentuk karakter dan peradaban di sekolah. Upaya peningkatan mutu pendidikan Islam tidak sekaligus, tetapi juga berdasarkan peningkatan mutu setiap komponen pendidikan. Fokus manajemen peningkatan mutu pendidikan terletak pada proses atau sistem pencapaian tujuan dari organisasi sekolah itu sendiri. Manajemen peningkatan mutu pendidikan Islam di sekolah adalah suatu upaya untuk meningkatkan mutu pendidikan Islam yang berpusat pada pendidikan sekolah itu sendiri, menerapkan sekumpulan teknik berdasarkan pada ketersedian data kuantitatif dan kualitatif, dan pemberdayaan semua unsur-unsur sekolah untuk secara berkelanjutan agar terjadi peningkatan meningkatkan kapasitas dan kemampuan organisasi sekolah untuk memenuhi kebutuhan peserta didik dan masyarakat.